Penerapan Metode SWOT-MAGIQ Sebagai Strategi Peningkatan Pelayanan Jasa Laundry - Relo Subagio; Erlin Windia Ambarsari; Rezkiyana Hikmah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Small and Medium-sized Laundry Service Enterprises face stiff competition and rapidly changing market dynamics in the contemporary business era. This study aims to understand the key factors influencing the success of Small and Medium-sized Laundry Service Enterprises through a SWOT analysis, focusing on strengths, weaknesses, opportunities, and threats. Using the Rank Order Centroid (ROC) method for criteria evaluation, this research found that